THE RELATIONSHIP OF KNOWLEDGE, ATTITUDE AND MOTHER'S BEHAVIOR TO THE FEEDING OF COMPLEMENTARY FOOD WITH NUTRITIONAL STATUS FOR TODDLER - Zahroturrosidah, Zahroturrosidah; Damayanti, Amilia Yuni; Pinasti, Ladyamayu; Fathimah, Fathimah (Universitas Darussalam Gontor, 2024)
Background: The problem of nutritional status in toddlers is the role of parents in providing good nutrition so that it is very influential because malnutrition and undernutrition in toddlers occurs through a long process and is determined by the fulfillment of nutritional needs. Objective: This study aims to determine the relationship between knowledge, attitudes and behavior of mothers related to complementary feeding with the nutritional status of toddlers. Method: This research method is analytic obeservational with a cross-sectional approach. The sampling technique was purposive sampling of 103 respondents collecting data using a questionnaire that is knowledge, attitudes, and behavior and measuring the nutritional status of toddlers using body weight according to age and height according to age. Bivariate analysis using the Gamma correlation test. Results: The results showed that the majority of respondents, had a nutritional status of 27.8% based on weight for age, a short nutritional status of 27.3% based on weight-for-age, maternal knowledge with the highest value of 28.3. While, maternal attitudes with the lowest value of 29.4% and maternal behavior with the lowest value of 29.9%. Knowledge with nutritional status based on weight-for-age and height-for-age p value 0.042 and p value 0.033. Attitude with nutritional status based on weight-for-age and height-for-age p value 0.076 and p value 0.063. Behavior with nutritional status based on weight-for-age and height-for-age p value 0.000 and p value 0.000. Conclusion: It can be concluded that there is a relationship between knowledge, and maternal behavior related to complementary feeding with the nutritional status of toddlers and there is no relationship between maternal attitudes related to complementary feeding with the nutritional status of toddlers in the working area of the Puskesmas Kauman Ngawi Regency.